Testing the validity of the purchasing power parity hypothesis: a study based on the RMB/USD exchange rate. (6th May 2010) - Yu, Chunjiao; Zhu, Longfei
The validity of the Purchasing Power Parity (PPP) hypothesis for estimation and determination of the RMB exchange rate is assessed empirically in this paper, which is based on the monthly data of RMB/USD nominal exchange rate, Chinese Consumer Price Index (CPI) and the US CPI from May 1994 to December 2006. The empirical test involves two steps: testing the 'strict' relative PPP and then the 'weak' relative PPP. The results indicate that the 'strict' relative PPP doesn't hold while the 'weak' one holds for RMB/USD exchange rate, which suggests that the variation of RMB/USD exchange rate has a tendency of reverting to the PPP level. This implies that the long-run PPP relationship holds for the RMB/USD exchange rate. But we find the regression equation testing the 'weak' relative PPP is not fitted well to that of the real fluctuation of RMB/USD exchange rate, which indicates the short-run deviation of RMB/USD exchange rate from the PPP equilibrium exchange rate. We argue that short-run impact of other macroeconomic variables besides the price index may cause the real exchange rate of RMB to deviate from the PPP equilibrium one. We thus propose some approaches to modify the PPP econometric model when applying it for estimating the RMB long-run equilibrium value or judging whether the RMB real exchange rate is at its appropriate level.